Low‐dose phase contrast tomography with conventional x‐ray sources. Issue 7 (24th June 2014) - Hagen, C. K.; Munro, P. R. T.; Endrizzi, M.; Diemoz, P. C.; Olivo, A.
Abstract : Purpose: The edge illumination (EI) x‐ray phase contrast imaging (XPCi) method has been recently further developed to perform tomographic and, thus, volumetric imaging. In this paper, the first tomographic EI XPCi images acquired with a conventional x‐ray source at dose levels below that used for preclinical small animal imaging are presented. Methods: Two test objects, a biological sample and a custom‐built phantom, were imaged with a laboratory‐based EI XPCi setup in tomography mode. Tomographic maps that show the phase shift and attenuating properties of the object were reconstructed, and analyzed in terms of signal‐to‐noise ratio and quantitative accuracy. Dose measurements using thermoluminescence devices were performed. Results: The obtained images demonstrate that phase based imaging methods can provide superior results compared to attenuation based modalities for weakly attenuating samples also in 3D. Moreover, and, most importantly, they demonstrate the feasibility of low‐dose imaging. In addition, the experimental results can be considered quantitative within the constraints imposed by polychromaticity. Conclusions: The results, together with the method's dose efficiency and compatibility with conventional x‐ray sources, indicate that tomographic EI XPCi can become an important tool for the routine imaging of biomedical samples.